Strategic Alternatives for Transforming Public Egyptian Universities to World-Class Universities - Ahmed, Hanaa Ouda Khadri (European Scientific Journal, ESJ, 2016)
In the past decade, the term “world-class university (WCU)” - also called “globally competitive universities”, “world-class”, “elite”, or “flagship” universities- has become a catch phrase. This is simply not only for improving the quality of learning and research in higher education, but is also more significant for developing the competency to compete in the global higher education marketplace through the acquisition and formation of advanced knowledge. The main objective of this paper is to propose strategic alternatives for transforming public Egyptian universities to world-class universities. In achieving this objective, the paper starts by attempting to construct an operational definition of a world-class university. Then, it outlines the features of world-class university, the requirements for transformation into world-class universities, the challenges involved in achieving world-class universities, and the key problems and challenges of the Egyptian higher education system. Finally, the selected statistical population of the research include higher education experts [N=57]. Thus, a mix method of using a questionnaire and conducting interviews were used. The research questions are: 1- What does it mean for a university to be a world-class university? 2-What are the essential features and characteristics of a world-class university? 3-How does the ecosystem influence the performance of universities? 4-What are the present performance, problems, and challenges of the Egyptian higher education system? 5-What are the higher education reform initiatives in Egypt? 6-What are the requirements that could upgrade public Egyptian universities to world-class universities? 7- What are the existing challenges of developing world-class universities? 8-What strategic alternatives have been developed for transforming public Egyptian universities to world-class universities? Therefore, one-Sample Kolmogorov-Smirnov Test was used to analyze the data. In addition, the result obtained in the study shows the use of collaborative strategic alternative rather than to upgrade the present Public universities, or create or merge them together.